Interaction of Lp(a) with Plasminogen Binding Sites on Cells - Miles, Lindsey A; Fless, Gunther M; Scanu, Angelo M; Baynham, Patricia; Sebald, Matthew T; Skocir, Pamela; Curtiss, Linda K; Levin, Eugene G; Hoover-Plow, Jane L; Plow, Edward F (Thrombosis and Haemostasis, 1995)
Lp(a) competes with plasminogen for binding to cells but it is not known whether this competition is due to the ability of Lp(a) to interact directly with plasminogen receptors. In the present study, we demonstrate that Lp(a) can interact directly with plasminogen binding sites on monocytoid U937 cells and endothelial cells. The interaction of Lp(a) with these sites was time dependent, specific, saturable, divalent ion independent and temperature sensitive, characteristics of plasminogen binding to these sites. The affinity of plasminogen and Lp(a) for these sites also was similar (Kd = 1-3 μM), but Lp(a) bound to fewer sites (̴10-fold less). Both gangliosides and cell surface proteins with car- boxy-terminal lysyl residues, including enolase, a candidate plasminogen receptor, inhibited Lp(a) binding to U937 cells. Additionally, Lp(a) interacted with low affinity lipoprotein binding sites on these cells which also recognized LDL and HDL. The ability of Lp(a) to interact with sites on cells that recognize plasminogen may contribute to the pathogenetic consequences of high levels of circulating Lp(a).